Recent Advances on Transition-Metal-Catalyzed Asymmetric C–H Arylation Reactions - Li, Mingliang; Wang, Jun (Synthesis, 2021)
Transition-metal-catalyzed asymmetric C–H functionalization has become a powerful strategy to synthesize complex chiral molecules. Recently, catalytic enantioselective C–H arylation has attracted great interest from organic chemists to construct aryl-substituted chiral compounds. In this short review, we highlight recent advances in asymmetric C–H arylation from 2019 to late 2021, including enantioselective C(sp2)–H arylation to construct axial or planar chiral compounds, and enantioselective C(sp3)–H arylation to introduce central chirality via desymmetrization of the methyl group or methylene C–H activation. These processes proceed with palladium, rhodium, iridium, nickel, or copper catalysts, and utilize aryl halides, boron, or diazo derivatives as arylation reagents.1 Introduction2 Transition-Metal-Catalyzed Asymmetric C(sp2)–H Arylation2.1 Chelation-Assisted Asymmetric C(sp2)–H Arylation for the Construction of Atropisomer2.2 Chelation-Assisted Asymmetric C(sp2)–H Arylation for the Construction of Planar Chiral Compounds2.3 Chelation-Assisted Asymmetric C(sp2)–H Arylation and Axial-to-Central Chirality Transfer for the Construction of Spirocycles2.4 Other Asymmetric C(sp2)–H Arylation Reactions3 Transition-Metal-Catalyzed Asymmetric C(sp3)–H Arylation3.1 Chelation-Assisted Enantioselective C(sp3)–H Arylation through Desymmetrization3.2 Chelation-Assisted Enantioselective Methylene C(sp3)–H Arylation3.3 Other Asymmetric C(sp3)–H Arylations4 Conclusion and Outlook
Keywords: C–H bond functionalization; transition-metal catalysis; asymmetric C–H activation; C(sp2)–H arylation; C(sp3)–H arylation; arylation; chiral ligands